COMPARATIVE ANALYSIS OF FINANCIAL PERFORMANCE OF CONVENTIONAL BANKING WITH BANKING SHARIA USING THE CAMELS METHOD BEFORE AND DURING THE ECONOMIC RECESSION DUE TO THE COVID PANDEMIC – 19 YEAR 2020 - Yuli Kurnia Firdausia; Siti Samsiyah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to analyze the comparison of the performance of Islamic banking and conventional banks before and during the Covid 19 pandemic using CAMELS. The data analysis method has been described in accordance with the method designed in this study to measure the health of the Bank, using CAMELS. The data used in this study is secondary data, namely the financial statements used to measure the performance of conventional banks and Islamic banks are financial statements for the period 2017-2020. The measured performance includes CAR, NPL, NPM, ROA, BOPO, LDR, IER from 10 Islamic and conventional banks used as samples in this study. The analytical tool used is multiple linear regression. To analyze the data obtained in this study, Microsoft Excel, SPSS and other software were used. Sampling in this study uses non-probability with purposive sampling method. Based on the results of the research that has been carried out, it is found that the results of the CAMEL Ratio Testing the CAR ratio between Islamic banks and conventional banks shows the results of P value 0.000 < (0.05). NPL ratio value P value 0.042 < (0.05). NPM ratio value Pvalue 0.175 > (0.05). ROA ratio value Pvalue 0.900 > (0.05). BOPO ratio value P value 0.044 < (0.05). LDR ratio value P value 0.000 < (0.05). The value of the ratio IER Pvalue 0.019 < (0.05). From the results of the analysis above, it can be concluded that the financial performance of Islamic banks and conventional banks during the Covid-19 pandemic period 2017-2020, namely there are significant differences in the ratio of Capital Adequacy Ratio (CAR), Non Performing Loans (NPL), Operating Costs to Operating Income (BOPO), Loan to Deposit Ratio (LDR), and Interest Expense Ratio (IER).